Effects of Noise Coherence on Stochastic Resonance Enhancement in a Bithreshold System - Litong, Marisciel; Hayakawa, Yoshinori; Sawada, Yasuji (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
We report a method of enhancing stochastic resonance (SR) that uses coherent noise in a symmetric bithreshold device. Coherent and non-coherent noise types are used to show that this method is feasible. The detection performance of the system is quantified based on the strength of the signal frequency in the power spectrum. We introduce a normalization condition of the different noise types so as to allow comparison of the results.